MTV, an ssDNA Protecting Complex Essential for Transposon-Based Telomere Maintenance in Drosophila. - Yi Zhang; Liang Zhang; Xiaona Tang; Shilpa R Bhardwaj; Jingyun Ji; Yikang S Rong (PLoS Genetics, 2016)
Multiple complexes protect telomeres. In telomerase-maintained organisms, Shelterin related complexes occupy the duplex region while the CST and Tpp1-Pot1 complexes bind the single stranded overhang of telomeres. Drosophila uses a transposon-based mechanism for end protection. We showed that the HOAP-HipHop complex occupies the duplex region. Whether an ssDNA-binding complex exists is not known. Here we discover a novel protein, Tea, that is specifically enriched at telomeres to prevent telomere fusion. We also identify a complex consisting of Tea and two known capping proteins, Ver and Moi. The Moi-Tea-Ver (MTV) complex purified in vitro binds and protects ssDNA in a sequence-independent manner. Tea recruits Ver and Moi to telomeres, and point mutations disrupting MTV interaction in vitro result in telomere uncapping, consistent with these proteins functioning as a complex in vivo. MTV thus shares functional similarities with CST or TPP1-POT1 in protecting ssDNA, highlighting a conserved feature in end protecting mechanisms.